Fabrication of microscale medical devices by two-photon polymerization with multiple foci via a spatial light modulator - Gittard, Shaun D. (Optical Society of America, 2011)
Two-photon polymerization is an appealing technique for producing microscale devices due to its flexibility in producing structures with a wide range of geometries as well as its compatibility with materials suitable for biomedical applications. The greatest limiting factor in widespread use of two-photon polymerization is the slow fabrication times associated with line-by-line, high-resolution structuring. In this study, a recently developed technology was used to produce microstructures by two-photon polymerization with multiple foci, which significantly reduces the production time. Computer generated hologram pattern technology was used to generate multiple laser beams in controlled positions from a single laser. These multiple beams were then used to simultaneously produce multiple microstructures by two-photon polymerization. Arrays of micro-Venus structures, tissue engineering scaffolds, and microneedle arrays were produced by multifocus two-photon polymerization. To our knowledge, this work is the first demonstration of multifocus two-photon polymerization technology for production of a functional medical device. Multibeam fabrication has the potential to greatly improve the efficiency of two-photon polymerization production of microscale devices such as tissue engineering scaffolds and microneedle arrays.